How COOL is U.S. Shrimp trade? - Joseph, Siny; Lavoie, Nathalie; Caswell, Julie (My University, 2014)
We investigate the economic impact of partial implementation of COOL on U.S. shrimp trade by developing a conceptual model that encompasses horizontal and vertical product differentiation. Horizontal differentiation is characterized by explicitly accounting for differences in shrimp processing – fresh or frozen versus peeled, canned, or breaded. Vertical differentiation in the conceptual model is captured by two scenarios – presence and absence of COOL – on trade between major shrimp exporters and United States. COOL implementation results in quality disclosure through origin labeling and additional costs of labeling on fresh and frozen shrimp sold at retail while processed shrimp products are excluded from labeling. The conceptual model indicates a change in product mix with COOL implementation: the relative share of processed shrimp increases when compared to unprocessed shrimp. Empirically testing the hypothesis using an econometric model shows there is no change in the product mix in the two scenarios. The results however change depending on the choice of variable used to proxy quality.
Keywords: Country of Origin Labeling; Shrimp; Trade